Правові засади кібербезпеки в Україні - Новік, Т. О. (ХНУРЕ, 2025)
In today's world, where digital technologies have become an integral part of society, cybersecurity is critically important. Ukraine is actively developing its legal framework for cybersecurity as part of its European integration and efforts to strengthen national security. The relevance of this topic is underscored by the growing number of cyber threats and their potential impact on national security, the economy, and citizens' rights. In 2023, there was a significant rise in cyber incidents, which calls for an enhancement of Ukraine’s cybersecurity system. Ukraine’s legal progress in cybersecurity aligns with European standards, but further harmonization and cooperation are needed for more comprehensive protection.
Keywords: кібербезпека; правові засади кібербезпеки